Komitmen Organisasional dan Organizational Citizenship Behavior (OCB) sebagai Pemediasi pada Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja Pegawai (Studi pada Dinas Pertanian dan Kehutanan Kabupaten Rembang) - Prima Kartika Sari; Euis Soliha (Forum Manajemen Indonesia (FMI), 2016)
This study aimed to analyze the effect of transformational leadership style to the organizational commitment, transformational leadership style to organizational citizenship behavior, organizational commitment on organizational citizenship behavior, organizational commitment to employee performance, transformational leadership style on employee performance and organizational citizenship behavior on employee performance. The sample used in this research is census method, the number of respondents was 103 employees at Dinas Pertanian dan Kehutanan Kabupaten Rembang. Data testing techniques used include test the validity of factor analysis, reliability test with Cronbach alpha formula, multiple regression analysis to validate the research hypothesis and test the mediation. From the test results show the transformational leadership style positive and significant effect on organizational commitment. Transformational leadership positive and significant effect on organizational citizenship behavior. Organizational commitment has no effect on organizational citizenship behavior. Organizational commitment positive and significant effect on employee performance. Transformational leadership style has no effect on employee performance. Organizational citizenship behavior positive and significant impact on employee performance. Organizational commitment and organizational citizenship behavior perfect mediate the effect of transformational leadership style on employee performance. Keywords: Transformational Leadership Style, Organizational Commitment, Organizational Citizenship Behavior, Employee Performance.